2019
DOI: 10.3390/w11102074
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Potential for Potable Water Savings in the Residential Sector of a City: A Case Study of Joinville City

Abstract: The objective of this study is to evaluate the potential for potable water savings by using rainwater in the residential sector of Joinville, a city located in southern Brazil. Data on roof areas of residential buildings were obtained from the Joinville city council. By considering the roof areas and typologies of residential buildings, representative models were created. The following parameters were used to determine the rainwater tank capacity: the number of dwellers; the total daily water demand per capita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…From all the strategies, the authors indicated that water-efficient fixtures were the best water reduction strategy, contributing 59% of the total water reduction. Custódio and Ghisi (2019) reported that the potential water savings were 18.5% when rainwater was used in toilets and 40.8% when rainwater was used in toilets and washing machines in Joinville (Brazil). Due to the sizable water savings that can be reached by implementing different conservation practices, the ORW and especially the Pereira/Dosquebradas urban area will benefit from implementing any of the approaches previously mentioned.…”
Section: Water Footprintsmentioning
confidence: 99%
“…From all the strategies, the authors indicated that water-efficient fixtures were the best water reduction strategy, contributing 59% of the total water reduction. Custódio and Ghisi (2019) reported that the potential water savings were 18.5% when rainwater was used in toilets and 40.8% when rainwater was used in toilets and washing machines in Joinville (Brazil). Due to the sizable water savings that can be reached by implementing different conservation practices, the ORW and especially the Pereira/Dosquebradas urban area will benefit from implementing any of the approaches previously mentioned.…”
Section: Water Footprintsmentioning
confidence: 99%
“…For example, a rainfall amount of only 640 mm/yr has a roofing area of 2450 m 2 in the paper of Custodio and Ghisi (2019), whereas in the study of Sámano-Romero et al ( 2016), a rainfall amount of 4239 mm/yr has a roofing area of only 50 m 2 which shows that the recorded rainfall amount is usually not the basis for computing the area of the roof. However, most buildings' roof spaces are not large enough to collect enough rainwater to meet demand [53]. Nevertheless, catchment area and catchment surface type can be changed to enhance system performance [54].…”
Section: Efficiency Of Treatmentmentioning
confidence: 99%
“…These raintank yield values represented median value from 10,000 stochastic simulation runs. Using a similar modelling approach considering 33,720 scenarios, Custodia and Ghisi [31] reported 41% of potable water saving when rainwater is used in toilets and washing machines.…”
Section: Desktop Assessment Of Rainwater Usage For Mains Water Savingmentioning
confidence: 99%